Implementation of Multimedia Presentations in Enhancing the Phonetic and Speaking Abilities of Kindergarten Pupils - Pullido, Cherrylyn Faith D.; Espiritu, Raymond D. (Future Science / FSH-PH Publications, 2026)
This study examined the impact of multimedia presentations on the development of auditory awareness and oral communication skills in kindergarten children, as perceived by teachers in the Subic District. Emphasizing the importance of phonological awareness as a foundational skill in early literacy, the research explored how multimedia tools such as interactive whiteboards, flashcards, and video content facilitated phonetic development and speaking abilities. A total of 49 kindergarten teachers participated in the study, which employed a descriptive survey method to collect data on teachers' demographics, the level of multimedia integration, and the challenges faced in implementing multimedia in the classroom. The findings revealed that the majority of respondents were young, female teachers with limited experience. Multimedia tools were reported to be